Posture in top-level Croatian rhythmic gymnasts and non-trainees - Radas, J.; Trost Bobic, T. (Kinesiology, 2011)
The main goal of the study was to determine the influence of the long-term rhythmic gymnastics training process on certain motor abilities and on the posture of elite Croatian rhythmic gymnasts. The sample was composed of 35 girls aged 12.89 (±2.32) years from Zagreb, Croatia. Fifteen of them were rhythmic gymnasts who have trained 8.93 hours per week on average, for at least 5 years. The control group consisted of 20 female pupils of the primary school "Borovje" who were not engaged in any regular sporting activity beside physical education classes. The measures consisted of 17 postural variables and 8 tests assessing motor abilities. The t-test for independent samples showed marked statisticaldifferences in arithmetic means between the two groups for all the motor variables. Mann-Whitney U test showed no differences between the two groups in all the posture variables, but one. The two groups differed significantly only in the variable kyphosis, showing that poor kyphotic posture was more frequent in non-trainees (p=.03). The variables Lorenz`s triangle and frontal shoulder position almost reached statistical significance (p=.06 and p=.07, respectively). Although the mentioned results failed to fall within the range of statistical significance, they are of substantial clinical importance, showing the tendency to a greater frequency of poor scoliotic posture in rhythmic gymnasts. The obtained results pointed out the positive side of sport: a good level of motor abilities and a minor incidence of poor kyphotic posture. Clinically, the results also indicate some sport-specific postural problems that may occur due to asymmetric overload. However, since statistical significance was not reached, there is a need to investigate further the influence of persistent asymmetric overloading of the spine on rhythmic gymnasts` posture.